Etimološke drobtine 1-5 - Snoj, Marko (Slavistična revija, 2003)
The article offers etymological solutions for the Slovene words jera, šimbas, trnič, usačnica and vintgar, for which to date there have been unsatisfactory or missing explanations.
Keywords: etimologija; etymology; prevzete besede; primerjalno jezikoslovje; Slovene; slovenščina